Bioluminescence and its application in the monitoring of antimicrobial photodynamic therapy - Alves, Eliana (2019)
Light output from bioluminescent microorganisms is a highly sensitive reporter of their metabolic activity and therefore can be used to monitor in real time the effects of antimicrobials. Antimicrobial photodynamic therapy (aPDT) is receiving considerable attention for its potentialities as a new antimicrobial treatment modality. This therapy combines oxygen, a nontoxic photoactive photosensitizer, and visible light to generate reactive oxygen species (singlet oxygen and free radicals) that efficiently destroy microorganisms. To monitor this photoinactivation process, faster methods are required instead of laborious conventional plating and overnight incubation procedures. The bioluminescence method is a very interesting approach to achieve this goal. This review covers recent developments on the use of microbial bioluminescence in aPDT in the clinical and environmental areas.